2018
DOI: 10.14744/eej.2018.29491
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic procedural errors by students in two Saudi dental schools

Abstract: To explore endodontic procedural errors committed by undergraduate dental students in King Khalid University (KKU), Abha and AlFarabi dental college, Riyadh. Methods: In this cross sectional study, a questionnaire was distributed to 500 dental students from both schools and of both genders in the 5th and 6th levels in the academic year 2016-2017. Participants were asked to record their endodontic procedural error(s) that had occurred during training. Results: Returned and eligible questionnaires were 469 (93.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
1
16
1
Order By: Relevance
“…(Table 3) Notwithstanding, there was no difference at other time intervals. Students are fully supervised by qualified clinicians in all situations; however, students have been found to have a higher rate of clinical errors than experienced clinicians [34]. The high rate of early denture replacements by students in this study may reflect the replacement of dentures in which procedural errors were identified and corrected by replacement of the dentures.…”
Section: Discussionmentioning
confidence: 77%
“…(Table 3) Notwithstanding, there was no difference at other time intervals. Students are fully supervised by qualified clinicians in all situations; however, students have been found to have a higher rate of clinical errors than experienced clinicians [34]. The high rate of early denture replacements by students in this study may reflect the replacement of dentures in which procedural errors were identified and corrected by replacement of the dentures.…”
Section: Discussionmentioning
confidence: 77%
“…This was in agreement with previous results. 15,16,17,18 Availability of flexible Ni Ti files and pre-curving techniques would be sufficient to negotiate most of the curved canals 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Failure to negotiate curvature is an indicator of the incompetency of the clinician. 15,16,17,18 Pulp stones obstruct the entry of instruments into the canal and calcification is one of the several reasons for short obturation. Modern technology is used well to remove the pulp stone and negotiate calcified canals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations